Habituation disorders in auditory middle latency response of persistent postural-perceptual dizziness patients - Murofushi, Toshihisa; Goto, Fumiyuki; Ushio, Munetaka (Frontiers in Neurology, 2024)
Objectives To study habituation disorders in auditory middle latency response (AMLR) to repetitive stimuli of persistent postural-perceptual dizziness (PPPD) patients. Subjects Twenty-eight PPPD (10 men and 18 women, mean 59.5 years of age, 26–81 years of age) were enrolled. For comparison, data of 13 definite vestibular migraine (VM) patients (3 men, 10 women, mean age 45.5), 13 definite unilateral Meniere’s disease (MD) patients (2 men, 11 women, mean age 50.6), and 8 healthy control (HC) subjects (2 men, 6 women, mean age 37.1) in the previous study were utilized. Methods The electrodes were placed on the vertex and the spinal process of the fifth cervical vertebra. Clicks (0.1 msec, 70 dB nHL) were binaurally presented and averaged (800 times). Averaged responses were divided into 4 sets (S1 to S4) according to the temporal order. As peaks, Na, and Pa were identified, and relative Na-Pa amplitudes in S2–S4 to S1 were analyzed. Results The mean relative amplitude of PPPD patients showed lack of habituation (potentiation) as shown in VM patients, although the extent of potentiation was weaker than VM. Comparison of relative S4 amplitudes showed significant differences among the 4 groups (p = 0.0013 one-way ANOVA), Multiple comparison revealed significant differences between PPPD and MD (p = 0.0337 Dunnet’s test). Conclusion PPPD patients showed lack of habituation (potentiation) of Na-Pa amplitude in AMLR to repetitive stimuli. Lack of habituation (potentiation) might be associated with sensory processing disorders in PPPD.